Pancreatic Stone Protein in patients with liver failure - Lopes, Diogo (2025)
Funding Information: We want to acknowledge the whole ICU, Transplant Unit, and General Surgery ward staff for their support in the collection of samples, Marta Alves, MSc (NOVA Medical School) for her support on statistics, and Abionic SA. Publisher Copyright: © 2025 Société Française d'Anesthésie et de Réanimation (SFAR)